Perancangan Sistem Kompensasi Ideal pada UKM Kedai Kopi XYZ Menggunakan Metode Point System berbasis Job Value - Putri, Amanda Pramesty; Riskita, Dhea Hadi; zahroh, Fatimatuz; Rahman, Iqbal Zulfikar; Zahara, Hurul Aini; Kartika, Lindawati (STIE DWI SAKTI BATURAJA, 2023)
An ideal compensation system is one aspect that influences employee satisfaction and performance. One of the SMEs in Batam City, namely XYZ Coffee Shop, has not implemented a specific compensation system in paying employees. Therefore, it is necessary to have an ideal compensation structure designed to create employee job satisfaction. This study aims to identify the compensation system, analyze the compensation factors, and develop an ideal compensation structure for UKM Coffee Shop XYZ. This research is a quantitative research. Data were analyzed using descriptive analysis and the Point System method. The results of the study show that UKM Kopi XYZ has not implemented an ideal compensation system for its employees. The compensation factors used are Education, Knowledge and Training, Work Experience, Physical Ability, Communication, Teamwork, Financial Responsibility and Physical Assets, Customer Service Orientation, Analysis and Problem Solving, and Planning and Coordination. An effective and efficient compensation system for the XYZ Coffee Shop SMEs is to use an overlapping compensation system.